Plasma properties, switchback patches, and low α-particle abundance in slow Alfvénic coronal hole wind at 0.13 au. Issue 1 (9th August 2021) - Woolley, Thomas; Matteini, Lorenzo; McManus, Michael D; Berčič, Laura; Badman, Samuel T; Woodham, Lloyd D; Horbury, Timothy S; Bale, Stuart D; Laker, Ronan; Stawarz, Julia E; Larson, Davin E
ABSTRACT: The Parker Solar Probe (PSP) mission presents a unique opportunity to study the near-Sun solar wind closer than any previous spacecraft. During its fourth and fifth solar encounters, PSP had the same orbital trajectory, meaning that solar wind was measured at the same latitudes and radial distances. We identify two streams measured at the same heliocentric distance (∼0.13 au) and latitude (∼–$3{_{.}^{°}}5$ ) across these encounters to reduce spatial evolution effects. By comparing the plasma of each stream, we confirm that they are not dominated by variable transient events, despite PSP's proximity to the heliospheric current sheet. Both streams are consistent with a previous slow Alfvénic solar wind study once radial effects are considered, and appear to originate at the Southern polar coronal hole boundary. We also show that the switchback properties are not distinctly different between these two streams. Low α -particle abundance (∼0.6 per cent) is observed in the encounter 5 stream, suggesting that some physical mechanism must act on coronal hole boundary wind to cause α -particle depletion. Possible explanations for our observations are discussed, but it remains unclear whether the depletion occurs during the release or the acceleration of the wind. Using a flux tube argument, we note that an α -particle abundance of ∼0.6 per cent in this low-velocity wind could correspond to an abundance of ∼0.9 per cent at 1 au. Finally, as the two streams roughly correspond to the spatial extent of a switchback patch, we suggest that patches are distinct features of coronal hole wind.